STRATEGI PENGELOLAAN APLIKASI PROPAM POLDA RIAU SEBAGAI MEDIA INFORMASI POLDA RIAU - Dio Prathama; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
At this time many violations committed by police personnel. Therefore, the public needs information media to convey criticism and report directly to the government, especially the Regional Police (Polda). In this case the Riau Police plays a role to provide a medium of communication is fast in responding to reports directly to the community. It is realized by the Riau police through the application Propam Polda Riau. Propam Polda Riau application in direct management by the division of Profession and Security (Propam) Polda Riau. Propam Polda Riau application is also used by Polda Riau to monitor the performance of Riau provincial police personnel this is also to mensuksekan vision and mission of Indonesian Police. This research to determine the management of Propam Polda Riau application and evaluation of application management Propam Polda RiauThis study used qualitative research methods. Subject of this research consisted of 7 informan. The purpose of this research is the strategy of application management Propam Polda Riau as information media Polda Riau. Data collection techniques used were interviews, observation and documentation. In reaching the validity of data in this study, the authors use triangulation.The result of the research shows that in the management of Propam Riau Police bid application make planning in management that is, objective, identification of target public and marketing application. Bid Propam Riau Police also formed a team to manage the application of propam of Riau Police consisting of 7 people to manage the application process that is 1 person from the paminal (super user) in charge of filtering the incoming report and keeping the confidentiality of the complainant,2 person from Provos section is in charge of investigation, 2 persons from wabprof part serve as operator of information delivery from Riau Police to the public and 2 others from IT application developer Propam Polda Riau. And all activities are coordinated directly by Head Propam Polda Riau. The Prophet Polda Riau Propinsi Propinsi Riau Polytechnic of Propam Police of Riau that is: the feedback is slow, still lack of human resources in the management, the aplication difficult to access because maintance.Keywords: Polda Riau Pekanbaru, Management, Cyber, Application